Dasar Pertimbangan Hukum Tindak Pidana Pengeroyokan: Kajian Ratio Decidendi Putusan Nomor 355/Pid.B/2017/PN Bkn - Annisa Diana Pratiwi; Yana Indawati (Jurnal Hukum Lex Generalis, 2025)
The crime of mob violence at the Bangkinang District Court has increased in the last 5 (five) years. Based on these reasons, decision No. 355/Pid.B/2017/PN Bkn, stated that the defendants were acquitted of all charges of the public prosecutor. The panel of judges in their decision stated that there was no intent or mens rea on the part of the defendants to commit the crime. During the trial, evidence was presented in the form of witnesses, experts and letters to support the victim's loss report. The results of the panel stated that by using the theory of judge's consideration, the theory of the crime of beating and the theory of evidence, the element of mens rea and the fulfillment of Article 170 paragraph (1) of the Criminal Code can be fulfilled. The decision should have been to punish the defendants in accordance with the provisions of Article 170 paragraph (1) of the Criminal Code.